2021
DOI: 10.1038/s41598-021-81230-7
|View full text |Cite
|
Sign up to set email alerts
|

A set of composite, non-redundant EEG measures of NREM sleep based on the power law scaling of the Fourier spectrum

Abstract: Features of sleep were shown to reflect aging, typical sex differences and cognitive abilities of humans. However, these measures are characterized by redundancy and arbitrariness. Our present approach relies on the assumptions that the spontaneous human brain activity as reflected by the scalp-derived electroencephalogram (EEG) during non-rapid eye movement (NREM) sleep is characterized by arrhythmic, scale-free properties and is based on the power law scaling of the Fourier spectra with the additional consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
71
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 68 publications
(63 reference statements)
10
71
1
Order By: Relevance
“…We calculated Rüger area global significance as follows: 1/3 of the descriptive significances at p=.05/3 =.017 AND/OR half of descriptive significances at p=.05/2=.025. In this study, we considered data Rüger area significant under the "AND" condition (65,66). , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We calculated Rüger area global significance as follows: 1/3 of the descriptive significances at p=.05/3 =.017 AND/OR half of descriptive significances at p=.05/2=.025. In this study, we considered data Rüger area significant under the "AND" condition (65,66). , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…1c) (Gao, 2016). 1/f activity was previously disregarded as noise, but recent studies have shown that it's slope and offset are correlated with cognition and behavior (Bódizs et al, 2021;Colombo et al, 2019;Freeman and Zhai, 2009;Gao et al, 2020;Lendner et al, 2020;Miller et al, 2009a;Ouyang et al, 2020;Podvalny et al, 2015;Waschke et al, 2021), age (Dave et al, 2018;Schaworonkow and Voytek, 2021;Voytek et al, 2015), pharmacological manipulation (Stock et al, 2019;Timmermann et al, 2019), and disease (Robertson et al, 2019;Veerakumar et al, 2019). Despite tracking such a broad range of biological and cognitive phenomena, the neural substrate(s) of 1/f activity remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, changes in the shape of 1/f activity in the brain have been linked to shifts in the balance between excitatory and inhibitory synaptic inputs in local neural circuits (Gao et al, 2017). Furthermore, although 1/f activity is often regarded as noise to be excluded before performing frequency-domain analyses (Gyurkovics et al, 2021), the shape parameters of 1/f activity have been found to be related to behavior and cognition (Bódizs et al, 2021;Clements, Bowie, et al, 2021;Immink et al, 2021;Lendner et al, 2020;Ouyang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%